Cardiac catheterization and percutaneus catheter in grown-up congenital heart diseases: single center experience at developing country (Faculty of Medicine Universitas Indonesia, 2018)
Background: Grown-up congenital heart disease (GUCH) patients are unique and challenges especially at developing country. The numbers of diagnostic as well as interventional cardiac catheterization procedures in GUCH patients are growing. The aim of this study was to report the outcome of cardiac catheterization including intervention procedure in GUCH.Methods: The descriptive study was conducted at Sanglah Hospital, Denpasar, Bali, Indonesia. All patients (age of more than 12 years) who underwent cardiac catheterization from 2011 until 2017 were included in this study. Patients, characteristic, types of catheter procedures, immediate complications, and outcomes were documented.Results: A total 54 subjects were included with median age of 23 years and 70% were female. The first symptom that brought patients to hospital is dyspnea 46% and palpitation 32%. Five subjects underwent a diagnostic catheter procedure and 49 (91%) diagnostic and catheter based interventions. Transcatheter interventions procedures included atrial septal defect (ASD) (success rate of 20 per 21), patent ductus arteriosus (PDA) (success rate of 16 per16), ventricular septal defect (VSD) (success rate of 9 per 9), pulmonal stenosis (PS) (success rate of 1 per 2), and aortic stenosis (AS) (success rate of 1 per 1). The complications encountered were transient dysrhythmias in 15 subjects, device embolization in 4 subjects, massive bleeding in 1 subject, and overall mortality in 2 subjects.Conclusion: The number of the catheterization interventions in GUCH was 91% and ASD device closure was the most common procedure. Transcatheter intervention has a high procedural success rates (96%) and low procedural-related complications.